2020
DOI: 10.1002/mbo3.1053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise frequency on the gut microbiota in elderly individuals

Abstract: Growing evidence has shown that exercise can affect the gut microbiota. The effects of exercise frequency on the gut microbiota in elderly individuals are still largely unknown. In the present study, samples from 897 elderly and 1,589 adult individuals (18–60 years old) from the American Gut Project were screened. Microbial diversity and composition were analyzed by QIIME2, and microbial function was predicted by PICRUSt2. The outcomes were further analyzed by STAMP. The analysis showed that the α‐diversity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 59 publications
2
49
1
Order By: Relevance
“…This is in contrast to previous findings where regular exercise and sustained levels of increased physical activity have been shown to enhance microbial diversity independent of diet [16,17,56]. Interestingly, a recent report shows that, even though regular exercise among older adults is important to maintain a stable gut microbiota, the α-diversity was not significantly different between older adults performing regular exercise compared to those who did not [57]. On a family level, a change in relative abundance of several bacterial families was observed, but not in the Ruminococcaceae family, to which F. prausnitzii belongs.…”
Section: Discussioncontrasting
confidence: 94%
“…This is in contrast to previous findings where regular exercise and sustained levels of increased physical activity have been shown to enhance microbial diversity independent of diet [16,17,56]. Interestingly, a recent report shows that, even though regular exercise among older adults is important to maintain a stable gut microbiota, the α-diversity was not significantly different between older adults performing regular exercise compared to those who did not [57]. On a family level, a change in relative abundance of several bacterial families was observed, but not in the Ruminococcaceae family, to which F. prausnitzii belongs.…”
Section: Discussioncontrasting
confidence: 94%
“…Generally, a higher diversity of the gut microbiota was associated with a better health status [102]. Several studies in humans indicated a higher inter-individual variability and a lower diversity of the gut microbiota in older individuals [101], although the latter was not confirmed in all studies [103]. Studies in professional athletes showed that a high physical exercise level [104,105] is associated with a higher α-diversity of the gut microbiota compared to controls.…”
Section: Association With α-Diversity Indicesmentioning
confidence: 98%
“…Thus, VO 2 max seems to be a good predictor of gut microbial diversity and metabolic function in healthy humans. Recent findings from the American Gut Project revealed that chronic exercise training benefits older adults by maintaining the stability of the gut microbiota (microbial composition and function) induced by aging [ 277 ]. Recent data demonstrated that masters athletes can be seen as a model of healthy aging also from the perspective of the microbiota [ 278 ].…”
Section: Nutritional Considerations For Masters Athletesmentioning
confidence: 99%